Case report: Co-occurrence of Wilson’s and Alexander’s diseases revealed by genetic analysis - Ge, Shufan; Sun, Lanting; Wang, Han; Yang, Wenming; Xuan, Qiaoyu; Hua, Daiping (Frontiers in Neurology, 2025)
Wilson’s disease (WD) and Alexander’s disease (AxD) are two prevalent genetic illnesses in clinical practice. However, cases of concurrent WD and AxD have not been reported. A mutation in the ATP7B gene causes improper copper metabolism, whereas AxD is caused by a mutation in the GFAP gene, which causes glial fibrillary acidic protein to accumulate in astrocytes. We present the first instance of concurrent WD and AxD in order to increase the diagnosis accuracy of this type of disease and provide a more precise treatment plan for the patient. A 10-year-old girl who appeared with diminished speech, limb weakness, trouble walking, and mental behavioral problems within the last 2 months. The patient’s copper biochemistry results and clinical manifestations supported the diagnosis of WD, however her uncommon bilateral frontal lobe cerebral white matter with considerable high signal in MRI differed from the normal neuroimaging presentations of WD. To clarify the patient’s diagnosis, we did whole-exome sequencing testing. To further clarify the patient’s diagnosis, we performed whole exome sequencing tests on the patient and her father and detected a single heterozygous mutation in the GFAP gene and a double heterozygous mutation in the ATP7B gene, with the two variant loci located on the same allele. Combined with the Leipzig score and characteristic MRI changes, the patient was diagnosed with co-morbid WD and AxD. The overlapping presentation of the two diseases on MRI suggests the importance of clinicians recognizing the features of both diseases. A comprehensive diagnostic strategy including genetic testing, neuroimaging, and detailed clinical evaluation is required.